SISTEM PENDIDIKAN ANAK USIA DINI DALAM KONSEP ISLAM (Analisis dalam Teoritis dan Praktis) - Buyung Surahman (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2018)
This article  aims  to reveal  how the  education system  developed for early childhood in the  Islamic concept, which  includes curriculum, methods and  evaluation of education. The method used  in this paper is descriptive quali- tative  method. The results of the  discussion indicate that  the  education that  should be given to early childhood, is to include; first, the  aqidah education, this  is given because Islam  puts  the  education of faith  in the  most  fundamental position, Second, the Education of worship, so that  someday they grow into beings who really piety, that  is the devout man to carry out all religious commands and  obedient also in steer  clear of any ban.  Third, moral education, in order to educate morals to the children, in addition to be given the right example, should also be shown about how to respect and to manners with fellow human beings. Islamic educational methods that can and should be applied to early child- hood educational activities are exemplary methods, methods of practice and  practice, game  methods, songs,  and  sto- ries, methods of targhib and tarhib, methods of praise and flattery and inculcation of good habits. The evaluation for the assessment of the educational process of children at an early age can be done in various ways, among others through the observation and recording of anecdotes which is a record of the attitude and behavior of children